Salmond and Corporate Theory - Farrar, John H (Victoria University of Wellington Law Review, 2008)
Salmond’s corporate theory was strongly influenced by Maitland and the German jurists of the late Nineteenth century. He did not receive their views uncritically and formulated his own theories in a pragmatic manner. His views on corporate theory and the State have been influential. As a judge he applied orthodox principles and made a useful analysis of the corporate constitution as it then existed.